What is "hospital resilience"? A scoping review on conceptualization, operationalization, and evaluation - Merette Khalil; Hamid Ravaghi; Dalia Samhouri; John Abo; Ahmed Ali; Hala Sakr; Alex Camacho (Frontiers Media S.A., 2022)
BackgroundCOVID-19 underscored the importance of building resilient health systems and hospitals. Nevertheless, evidence on hospital resilience is limited without consensus on the concept, its application, or measurement, with practical guidance needed for action at the facility-level.AimThis study establishes a baseline for understanding hospital resilience, exploring its 1) conceptualization, 2) operationalization, and 3) evaluation in the empirical literature.MethodsFollowing Arksey and O'Malley's model, a scoping review was conducted, and a total of 38 articles were included for final extraction.Findings and discussionIn this review, hospital resilience is conceptualized by its components, capacities, and outcomes. The interdependence of six components (1) space, 2) stuff, 3) staff, 4) systems, 5) strategies, and 6) services) influences hospital resilience. Resilient hospitals must absorb, adapt, transform, and learn, utilizing all these capacities, sometimes simultaneously, through prevention, preparedness, response, and recovery, within a risk-informed and all-hazard approach. These capacities are not static but rather are dynamic and should improve continuously occur over time. Strengthening hospital resilience requires both hard and soft resilience. Hard resilience encompasses the structural (or constructive) and non-structural (infrastructural) aspects, along with agility to rearrange the space while hospital's soft resilience requires resilient staff, finance, logistics, and supply chains (stuff), strategies and systems (leadership and coordination, community engagement, along with communication, information, and learning systems). This ultimately results in hospitals maintaining their function and providing quality and continuous critical, life-saving, and essential services, amidst crises, while leaving no one behind. Strengthening hospital resilience is interlinked with improving health systems and community resilience, and ultimately contributes to advancing universal health coverage, health equity, and global health security. The nuances and divergences in conceptualization impact how hospital resilience is applied and measured. Operationalization and evaluation strategies and frameworks must factor hospitals' evolving capacities and varying risks during both routine and emergency times, especially in resource-restrained and emergency-prone settings.ConclusionStrengthening hospital resilience requires consensus regarding its conceptualization to inform a roadmap for operationalization and evaluation and guide meaningful and effective action at facility and country level. Further qualitative and quantitative research is needed for the operationalization and evaluation of hospital resilience comprehensively and pragmatically, especially in fragile and resource-restrained contexts.